Jump darling [videorecording (DVD)] - Connell, Phil; Leachman, Cloris; Duplessie, Thomas; Eastwood, Jayne; Kash, Linda, 1967- (Breaking Glass Pictures, 2022)
After a disastrous non-debut at a Toronto drag club, Russell leaves his status-conscious boyfriend and takes shelter with his grandmother Margaret in Canadian wine country. Margaret is a woman coming to terms with her mortality while determined to hang on to her independence. As tempers wear thin and family secrets are revealed, Russell and Margaret fight to maintain their dignity while being true to themselves.